Emancipated, Empowered, & Employable: Middle Eastern Women’s Transformative Experiential Learning - Shelbee R. Nguyen (Adult Education Research Conference, 2014)
Critical reflection journals were employed to promote thinking about global citizenship and the meaning of social justice for Middle Eastern learners enrolled in a short-term study abroad course. Analyses of private reflections reveal general cognitive reordering, socially constructed ideals of justice, and themes related to empowerment for Middle Eastern women.